Основні етапи створення 3d-персонажів - Логвиненко, Д. В. (ХНУРЕ, 2024)
This work is devoted to the main stages of creating three-dimensional char acters, which have become a necessary component of virtual reality and the computer graphics industry. A look at each stage – from concept to final realization – helps reveal the key insights and challenges involved in creating 3D char acters. Starting with the idea and concept, moving through the modeling and texturing phase, ending with animation and visualization, this analysis highlights the importance of harmoniously combining creativity with modern technical achievements.
Keywords: 3d-персонаж; 3D char acters